Nitrogen and Phosphorous Movement Characteristic in Terrace Paddy Field Using Cascade Irrigation System in West Sumatra, Indonesia - Darmawan, .; Yasin, Syafrimen; Masunaga, Tsugiyuki (JOURNAL OF TROPICAL SOILS, 2011)
West Sumatra is one of Indonesian rice bowl. The landscape of this province dominated by mountainous area with beautiful terrace paddy field lied from the middle slope to the lowland. The most common rice cultivation management in this area is application of cascade irrigation system with blanked amount of chemical fertilizer application. This study intends to figure out, whether this kind of paddy field management sustains and friendly to the environment or not. The results showed that cascade irrigation system created some discrepancies in suspended solid (SS), dissolve organic matter (DOM) and the nutrient movement characteristic a long the slope. The SS and DOM load and discharge strongly influenced by land preparation activities, while total and available nitrogen (N) and phosphorous (P) affected by chemical fertilizer application. In the upper part, the amount of chemical fertilizer seemed sufficient, indicated by negative amount of nutrient balance, while lower terrace show some indication of excess nutrient input. To avoid some demerit of cascade irrigation system, chemical fertilizer application should be base on site specific characteristic and taking into account of natural source contribution.Keywords: Cascade irrigation, chemical fertilizer, nutrient balance, terrace paddy field